Accuracy of Narrow-Band Imaging International Colorectal Endoscopic Classification for Predicting the Histology of Colon Polyps by Experienced Endoscopists and Trainees - Ramón Mena-Ramírez,; Andres Macari-Jorge,; Eva Juárez-Hernández,; Misael Uribe,; Iván López-Méndez, (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Digital chromoendoscopy has proven to be useful in the histological prediction of premalignant lesions in the colon. The aim of the study was to describe the diagnostic performance of Narrow-Band Imaging International Colorectal Endoscopic Classification in the histological differentiation of colonic lesions, applied by expert endoscopists and trainees.Materials and Methods: Cross-sectional study that includes high-definition endoscopic images and histopathological reports of 94 patients over 50 years. Images were evaluated and classified as Narrow-Band Imaging International Colorectal Endoscopic 1, 2, or 3 by 2 experts and 2 trainee endoscopists, all of them blinded to histological results. Diagnostic accuracy for each Narrow-Band Imaging International Colorectal Endoscopic category was calculated for trainees and expert endoscopists. Intra-observer agreement was evaluated by means of Cohen’s kappa coefficient; meanwhile, inter-observer agreement was calculated by means of Fleiss’ kappa.Results: Evaluations performed by expert and trainee endoscopists showed a performance for Narrow-Band Imaging International Colorectal Endoscopic category 1: sensitivity 62%, specificity 85%, area under receiver operator characteristic 0.73; Narrow-Band Imaging International Colorectal Endoscopic category 2: sensitivity 61%, specificity 73%, area under receiver operator characteristic 0.66; and Narrow-Band Imaging International Colorectal Endoscopic category 3: sensitivity 88%, specificity 91%, area under receiver operator characteristic 0.86. The total agreement of the evaluations was 72.5%, with an inter-observer variability of K 0.60 (95% CI 0.52-0.74). When the diagnostic performance for non-dysplastic lesions and dysplastic lesions (Narrow-Band Imaging International Colorectal Endoscopic 1 vs 2 and 3) was compared, we observed an increase in sensitivity for differentiated adenomas (Narrow-Band Imaging International Colorectal Endoscopic 2).Conclusion: Narrow-Band Imaging International Colorectal Endoscopic Classification applied in the histological prediction of static images of colonic lesions has a good diagnostic performance for Narrow-Band Imaging International Colorectal Endoscopic category 3, as well as an acceptable performance for Narrow-Band Imaging International Colorectal Endoscopic category 1, with a moderate agreement among observers.Cite this article as: Mena-Ramírez R, Macari-Jorge A, Juárez-Hernández E, Uribe M, López-Méndez I. Accuracy of narrow-band imaging international colorectal endoscopic classification for predicting the histology of colon polyps by experienced endoscopists and trainees. Turk J Gastroenterol. 2023;34(8):866-872.